Junctional Adhesion Molecule 3 Expression in the Mouse Airway Epithelium Is Linked to Multiciliated Cells - Mateos-Quiros, Clara Maria; Garrido-Jimenez, Sergio; Álvarez-Hernán, Guadalupe; Diaz-Chamorro, Selene; Barrera-Lopez, Juan Francisco; Francisco-Morcillo, Javier; Roman, Angel Carlos; Centeno, Francisco; Carvajal-Gonzalez, Jose Maria (Frontiers in Cell and Developmental Biology, 2021)
Tight-junction (TJ) proteins are essential for establishing the barrier function between neighbor epithelial cells, but also for recognition of pathogens or cell migration. Establishing the expression pattern and localization of different TJ proteins will help to understand the development and physiology of the airway. Here we identify that the junctional adhesion molecule 3 (Jam3) expression is restricted to multiciliated cells (MCCs) in the airway epithelium. In vitro, Jam3 expression varies along airway basal stem cell (BSC) differentiation and upon DAPT treatment or IL6 exposure. However, Jam3 is not required for BSC differentiation to specific cell types. In addition, we found that MCC lacking Jam3 display normal cilia morphology and cilia beating frequency with a delay in BB assembly/positioning in MCCs during differentiation. Remarkably, Jam3 in MCC is mostly localized to subapical organelles, which are negative for the apical recycling endosome marker Rab11 and positive for EEA1. Our data show that Jam3 expression is connected to mature MCC in the airway epithelium and suggest a Jam3 role unrelated to its known barrier function.